KEDUDUKAN FATWA DSN DALAM TATA HUKUM NASIONAL - Ichwan Ahnaz Alamudi; Ahmadi Hasan (Mitsaqan Ghalizan, 2023)
The Sharia economy grows in line with the demands of the Muslim community, which wants an economy that competes with the capitalist economy. Of course this struggle is not as easy as turning your palms. Political, sociological, huokum struggles also colored the emergence of regulations that banks Shariah in Indonesia. With the system of non-Islamic states, it must be difficult for the sharia banking to conduct transactions in accordance with the law of fiction that is written in the Islamic books. The product of the sharial banking that is "forced" to resemble the conventional banking product must have an influence on the concept of the theory of akad in the classical fiction. This DSN-MUI fatwa will become a positive law when adopted in regulations approved by law, as adopted as a judge's opinion in its decision, or adopted by the Bank of Indonesia Regulations, OJK Regulations and others. The DSN-MUI Fatwa plays a major role in the development of the Shariah economy